La santé en situation linguistique minoritaire - Bouchard, Louise; Gaboury, Isabelle; Chomienne, Marie-Hélène; Gilbert, A.; Dubois, L. (Politiques de Santé, 2009)

La parole aux communautés : nous sommes là! La vitalité des communautés de langues officielles en situation minoritaire. Rapport du Comité permanent des langues officielles - Lauzon, Guy (Gouvernement du Canada, Chambre des communes 39e Législature, 1er session, 2007)

Contribution Program to improve access to health services for Official Language Minority Communities. Formative evaluation. - Official Language Community Development Bureau (Health Canada, 2007)

Accès aux services de santé et aux services sociaux en anglais au Québec. Rapport de données de base 2005-2006 - Pocock, Joanne (Réseau communautaire de santé et de services sociaux, 2006)

Culture, language and self- assesments of future health: Anglophones and Francophones in Quebec’s Eastern Townships - Stout, Dale; Charpentier, Claude; Chiasson, Myriam; Filion, Emmalie (Journal of Eastern Townships Studies, 2009)
This study examines subjective ratings of health (SRH) by Francophones and Anglophones living in the Eastern Townships. Global self-ratings of health are regarded as sensitive predictors of future health states, mortality, functional decline and disability, and utilization of the health-care system. Yet despite their pragmatic value, SRH are poorly understood. Along with a spontaneous monitoring of present health states, culture and language are listed as determinants of SRH. Few studies exist, however, that clearly delineate the direction and degree of effect that culture and language have on SRH. Adopting a temporal assessment of SRH, we asked 358 Anglophones (N=176) and Francophones (N=171) from the Eastern Townships, aged 18 to 95, to rate their health in the past, present, and future. To isolate culture and language effects we also asked participants to rate their future health if they “remained in Quebec”. Results revealed a significant interaction between age and temporal ratings of health (SRH). Turning to the effects of location (unspecified or “in Quebec”) on future health ratings, there was a significant interaction with language. Post hoc tests revealed no significant differences in Francophones’ future health ratings (unspecified or “in Quebec”) but a significant ratings drop was noted for Anglophones if they “remained in Quebec”. After controlling for bilingualism, this interaction remained statistically significant.

The effects of age and culture on subjective well-being: A case study in the Eastern Townships - Stout, Dale; Filion, Emmalie; Chiasson, Myriam; de Man, Anton; Charpentier, Claude; Pope, Megan (Journal of Eastern Townships Studies, 2008)
The present study of diachronous ratings of subjective well-being (SWB) was modeled on research undertaken by Staudinger, Bluck & Herzberg (2003). In addition, we were interested in determining the effects of culture and context (where one lives) on SWB ratings. To gage these effects, we included the factor of mother tongue and altered the Life Satisfaction Questionnaire by adding a question concerning expected well-being in Quebec. We asked 350 Anglophones and Francophones from the Eastern Townships, aged 18 to 95, to rate their SWB in the past, present, future, and future ‘in Quebec’. The results concerning the effects of chronological age on diachronistic SWB ratings followed the patterns of previous research: young people (aged 18–38) rate past SWB lower than present SWB and future SWB much higher; middle-aged people (aged 39–64) rate their SWB the same regardless of time; And the elderly (67–95) rated past SWB higher than the present and their future SWB much lower. There were no differences between Anglophones or Francophones. Further analysis revealed the disturbing finding that the oldest participants rated their current SWB significantly lower than the other two age groups. In the second half of our study we found that by simply asking Francophones and Anglophones to rate their SWB in the future – first unspecified as to location, and then in a future ‘if they stay in Quebec’ – produced different response patterns. Both future SWB ratings were the same for Francophones, indicating that the questions were simply redundant. The Anglophones, on the other hand, rated their future SWB in Quebec consistently lower than an unspecified future.